Tinjauan Literatur: Model Literasi Keuangan UMKM dan Rumah Tangga Pesisir Berbasis Ekonomi Biru di Ohoi Tetoat Maluku Tenggara - Ansye Tuhumury (Management and Entrepreneurship Journal (MEJ), 2026)
This study aims to develop a model to strengthen financial literacy among coastal households and UMKM, grounded in the blue economy of Ohoi Tetoat, Southeast Maluku Regency. Referring to the situation in Ohoi Tetoat, which has abundant coastal and marine resources and unique local cultural wealth, but has not been optimally managed due to the community's low financial literacy and income instability. This study employs a systematic literature review following PRISMA guidelines, based on an analysis of 15 selected articles published in the past 10 years. The results of the study show that financial literacy plays an important role in improving financial management, access to financing, and business risk management. However, previous studies still treat financial literacy and the blue economy as separate. This study offers an integrative community-based model that combines financial literacy and blue economy principles to strengthen coastal economic resilience. This model is expected to serve as the basis for policies that empower coastal communities sustainably